Composite conductive film and preparation method thereof, photoelectric device and preparation method thereof, and display device

By applying a protective layer with hydrophilic and hydrophobic groups on the electrodes of the optoelectronic devices, the problem of electrode materials being susceptible to water and oxygen corrosion is solved, and the stability and corrosion resistance are achieved, and the device life is extended.

CN119852008APending Publication Date: 2025-04-18GUANGDONG JUHUA RES INST OF ADVANCED DISPLAY +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202311347789.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-17
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

The electrode materials of existing optoelectronic devices are susceptible to external environments such as water and oxygen, resulting in reduced device performance and shortened service life.

Method used

A composite conductive film is used, which includes a conductive layer and a protective layer on its surface, and the material of the protective layer comprises a material having hydrophilic and hydrophobic groups or a material having polar and non-polar groups. With this structure, the protective layer can effectively prevent the erosion of water and oxygen.

Benefits of technology

It improves the stability and corrosion resistance of optoelectronic devices, extends the life of the device, and enhances the oxidation resistance of the electrodes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119852008A_ABST
    Figure CN119852008A_ABST
Patent Text Reader

Abstract

The invention discloses a composite conductive film and a preparation method thereof, a photoelectric device and a preparation method thereof, and a display device. The composite conductive film comprises a conductive layer and a protective layer arranged on at least one surface of the conductive layer; the material of the protective layer comprises a material with a hydrophilic group and a hydrophobic group; or the material of the protective layer comprises a material with a polar group and a non-polar group. The protective layer is arranged in the composite conductive thin film, so that the composite conductive thin film has relatively high stability and corrosion resistance, and the conductive layer is effectively protected from being eroded by external environments such as water, oxygen and the like. The photoelectric conversion efficiency of the photoelectric device is remarkably improved, and the service life of the device is remarkably prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of optoelectronic devices, and more specifically, to a composite conductive film and a preparation method thereof, an optoelectronic device and a preparation method thereof, and a display device. Background Art

[0002] Since optoelectronic devices require current driving to work, electrodes are widely used in various optoelectronic devices.

[0003] However, the electrode materials commonly used today are easily corroded by external environments such as water and oxygen, causing oxidation and corrosion, which can lead to decreased device performance and shortened device life. Summary of the invention

[0004] Based on this, the object of the present invention is to provide a composite conductive film and a preparation method thereof, an optoelectronic device and a preparation method thereof, and a display device.

[0005] In order to achieve the above-mentioned object, the present application provides a composite conductive film, comprising a conductive layer and a protective layer disposed on at least one surface thereof; the material of the protective layer comprises a material having a hydrophilic group and a hydrophobic group; or

[0006] The material of the protective layer includes a material having a polar group and a non-polar group.

[0007] Optionally, in some embodiments of the present application, the material having a hydrophilic group and a hydrophobic group includes a surfactant; and / or the material of the protective layer includes a surfactant and an oxidant; and / or

[0008] The volume ratio of the oxidant to the surfactant is 1:(1-3).

[0009] Optionally, in some embodiments of the present application, the oxidant includes a hydrophilic oxidant, and the hydrophilic oxidant includes one or more of ferric sulfate and copper sulfate; and / or

[0010] The surfactant includes one or more of cetyltrimethylammonium bromide, cetyltrimethylammonium chloride, and sodium dodecyl sulfate.

[0011] Optionally, in some embodiments of the present application, the polar group includes an ester group; and / or the non-polar group includes at least one of an alkenyl group, an alkyl group, and a phenyl group; and / or

[0012] The material having polar groups and non-polar groups includes at least one of diethyl maleate, vinyl acetate, methyl acrylate, ethyl acrylate, methyl methacrylate, styrene, methyl methacrylate, and ethyl methacrylate; and / or

[0013] The material of the protective layer is any of the following:

[0014] (a) the material of the protective layer includes diethyl maleate and vinyl acetate, and the volume ratio of diethyl maleate to vinyl acetate is 1:(1-3);

[0015] (b) the material of the protective layer includes methyl acrylate and ethyl acrylate, and the volume ratio of methyl acrylate to ethyl acrylate is 1:(1-3);

[0016] (c) the material of the protective layer includes methyl methacrylate and styrene, and the volume ratio of methyl methacrylate to styrene is 1:(1-3);

[0017] (d) The material of the protective layer includes methyl methacrylate and ethyl methacrylate, and the volume ratio of methyl methacrylate to ethyl methacrylate is 1:(1-3).

[0018] Optionally, in some embodiments of the present application, at least one surface of the conductive layer has hydroxyl groups, and the protective layer is disposed on the surface of the conductive layer having hydroxyl groups; and / or

[0019] At least part of the hydroxyl groups on the surface of the conductive layer are connected to the hydrophilic groups via chemical bonds; and / or

[0020] The thickness ratio of the protective layer to the conductive layer is (10-30):(80-120).

[0021] Optionally, in some embodiments of the present application, the conductive layer includes a doped metal oxide particle electrode, a composite electrode, a graphene electrode, a carbon nanotube electrode, a metal element electrode or an alloy electrode, the material of the doped metal oxide particle electrode includes one or more of indium-doped tin oxide, fluorine-doped tin oxide, antimony-doped tin oxide, aluminum-doped zinc oxide, gallium-doped zinc oxide, indium-doped zinc oxide, magnesium-doped zinc oxide and aluminum-doped magnesium oxide, the composite electrode includes one or more of AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, TiO2 / Ag / TiO2, TiO2 / Al / TiO2, ZnS / Ag / ZnS or ZnS / Al / ZnS, and the material of the metal element electrode includes one or more of Ag, Al, Cu, Mo, Au, Pt, Ca, Mg and Ba.

[0022] The present application provides a method for preparing a composite conductive film, comprising the following steps:

[0023] providing a conductive layer;

[0024] Providing a protective layer precursor solution, wherein the protective layer precursor solvent includes a protective layer material, the protective layer material includes a material having a hydrophilic group and a hydrophobic group or the protective layer material includes a material having a polar group and a non-polar group;

[0025] Disposing the protective layer precursor solution on at least one surface of the conductive layer to form a protective layer precursor;

[0026] The protective layer precursor is heated to obtain a protective layer.

[0027] Optionally, in some embodiments of the present application, the material having a hydrophilic group and a hydrophobic group includes a surfactant; and / or

[0028] The material of the protective layer includes a surfactant and an oxidant; and / or

[0029] The volume ratio of the oxidant to the surfactant is 1:(1-3); and / or

[0030] The oxidant comprises a hydrophilic oxidant, and the hydrophilic oxidant comprises one or more of ferric sulfate and copper sulfate; and / or

[0031] The surfactant includes one or more of cetyltrimethylammonium bromide, cetyltrimethylammonium chloride, and sodium dodecyl sulfate; and / or

[0032] The polar group includes an ester group; and / or the non-polar group includes at least one of an alkenyl group, an alkyl group, and a phenyl group; and / or

[0033] The material having polar groups and non-polar groups includes at least one of diethyl maleate, vinyl acetate, methyl acrylate, ethyl acrylate, methyl methacrylate, styrene, methyl methacrylate, and ethyl methacrylate; and / or

[0034] The concentration of the protective layer precursor solution is 0.05-0.1M; and / or

[0035] The heating temperature is 50-70° C. and the heating time is 5-20 min.

[0036] Optionally, in some embodiments of the present application, the protective layer precursor solution further comprises an organic solvent, and the organic solvent comprises an alcohol solvent, chloroform, chlorobenzene, toluene; and / or

[0037] The alcohol solvent includes one or more of ethanol, propanol, butanol and pentanol.

[0038] Optionally, in some embodiments of the present application, at least one surface of the conductive layer has hydroxyl groups, and the protective layer precursor solution is disposed on the surface of the conductive layer having hydroxyl groups; and / or

[0039] At least one surface of the conductive layer is subjected to hydroxylation treatment to form the hydroxylated conductive layer surface and / or

[0040] After the protective layer precursor solution is disposed on at least one surface of the conductive layer, the composite conductive film is dried.

[0041] Optionally, in some embodiments of the present application, the hydroxylation treatment includes performing an acid wash treatment on at least one surface of the conductive layer; and / or

[0042] The pickling treatment comprises placing an acid solution on at least one surface of the conductive layer, leaving it to stand for 20 to 40 minutes, and then cleaning the surface of the conductive layer; and / or

[0043] The acidic solution includes concentrated acid; the concentration of the concentrated acid is 1.6-4 g / ml, and the concentrated acid includes one or more of concentrated nitric acid, concentrated sulfuric acid, and concentrated hydrochloric acid; and / or

[0044] The drying process includes providing an inert gas to dry the surface of the composite conductive film; the inert gas includes nitrogen, helium, and argon.

[0045] The present application provides a photoelectric device, comprising a bottom electrode and a top electrode, wherein at least one of the top electrode and the bottom electrode comprises the composite conductive film described above, or comprises the composite conductive film prepared by the above preparation method.

[0046] Optionally, in some embodiments of the present application, the photoelectric device further includes an electronic functional layer disposed between the bottom electrode and the top electrode, the electronic functional layer including an electron transport layer and / or an electron injection layer, the materials of the electron transport layer and / or the electron injection layer respectively including inorganic materials and / or organic materials; the inorganic material includes one or more of doped or undoped zinc oxide, barium oxide, nickel oxide, titanium oxide, tin oxide, tantalum oxide, zirconium oxide, nickel oxide, lithium titanium oxide, zinc aluminum oxide, zinc manganese oxide, zinc tin oxide, lithium zinc oxide, indium tin oxide, cadmium sulfide, zinc sulfide, molybdenum sulfide, tungsten sulfide, copper sulfide, zinc tin, indium phosphide, gallium phosphide, copper indium sulfide, copper gallium sulfide, and barium titanate, and the doped elements include one or more of aluminum, magnesium, lithium, manganese, yttrium, lanthanum, copper, nickel, zirconium, cerium, and gadolinium; the organic material includes one or more of quinoxaline compounds, imidazole compounds, triazine compounds, fluorene compounds, and hydroxyquinoline compounds; and / or

[0047] The photoelectric device also includes a light-emitting layer disposed between the bottom electrode and the top electrode, wherein the material of the light-emitting layer includes one or more of an organic light-emitting material and a quantum dot light-emitting material, wherein the organic light-emitting material includes 4,4'-bis(N-carbazole)-1,1'-biphenyl:tri[2-(p-tolyl)pyridine iridium(III), 4,4',4"-tri(carbazole-9-yl)triphenylamine:tri[2-(p-tolyl)pyridine iridium, diaromatic anthracene derivatives, distilbene aromatic derivatives, pyrene derivatives, fluorene derivatives, TBPe fluorescent materials, TTPX fluorescent materials, TBRb fluorescent materials, DBP One or more of fluorescent materials, delayed fluorescent materials, TTA materials, thermally activated delayed materials, polymers containing BN covalent bonds, hybrid localized charge transfer excited state materials, exciplex luminescent materials, polyacetylene and its derivatives, polyparaphenylene and its derivatives, polythiophene and its derivatives, polyfluorene and its derivatives, the quantum dot luminescent materials include one or more of single structure quantum dots, core-shell structure quantum dots and perovskite semiconductor materials, the materials of the single structure quantum dots, the core materials of the core-shell structure quantum dots and the shell materials of the core-shell structure quantum dots include II-VI compounds, IV-VI compounds, respectively. , at least one of a III-V compound and a I-III-VI compound, the II-VI compound comprising CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, CdSeS, CdSeTe, CdSTe, ZnSeS, ZnSeTe, ZnSTe, HgSeS, HgSeTe, HgSTe, CdZnS, CdZnSe, CdZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, Cd at least one of ZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe and HgZnSTe, the IV-VI group compound comprises at least one of SnS, SnSe, SnTe, PbS, PbSe, PbTe, SnSeS, SnSeTe, SnSTe, PbSeS, PbSeTe, PbSTe, SnPbS, SnPbSe, SnPbTe, SnPbSSe, SnPbSeTe and SnPbSTe,The III-V compounds include GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, GaNP, GaNAs, GaNSb, GaPAs, GaPSb, and AlN P, AlNAs, AlNSb, AlPAs, AlPSb, InNP, InNAs, InNSb, InPAs, InPSb, GaAlNP, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInN The compound of Group I-III-VI comprises at least one of CuInS2, CuInSe2 and AgInS2; the perovskite semiconductor material comprises a doped or undoped inorganic perovskite semiconductor, or an organic-inorganic hybrid perovskite semiconductor; the inorganic perovskite semiconductor has a general structural formula of AMX3, wherein A is Cs, + ions, M is a divalent metal cation, including Pb 2+ Sn 2+ , Cu 2+ 、Ni 2+ 、Cd 2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2+ 、Eu 2+ At least one of X is a halogen anion including Cl - Br - ,I - At least one of the following; the general structural formula of the organic-inorganic hybrid perovskite semiconductor is BMX3, wherein B is an organic amine cation, including CH3(CH2) n-2 NH3 + or [NH3(CH2) n NH3] 2+ , where n≥2, M is a divalent metal cation, including Pb 2+ Sn 2+ , Cu 2+ 、Ni 2 + 、Cd 2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb2+ 、Eu 2+ At least one of X is a halogen anion including Cl - Br - ,I - At least one of; and / or

[0048] The photoelectric device further comprises a hole functional layer disposed between the bottom electrode and the top electrode, the hole functional layer comprising a hole transport layer and / or a hole injection layer, the material of the hole transport layer and the material of the hole injection layer respectively and independently comprising 4,4'-N,N'-dicarbazolyl-biphenyl, N,N'-diphenyl-N,N'-bis(1-naphthyl)-1,1'-biphenyl-4,4"-diamine, N,N'-diphenyl-N,N'-bis(3-methylphenyl)-(1,1'-biphenyl)-4,4'-diamine, N,N'-bis(3-methylphenyl)-N,N'-bis(phenyl)-spiro, N,N'-bis(4-(N,N'-diphenyl-amino)phenyl)-N,N'-diphenylbenzidine, 4,4',4'-tri(N-carbazolyl)-triphenylamine, 4,4',4'-tri(carbazol-9-yl)triphenylamine, trichloroisocyanuric acid, terbium-doped phosphate-based green luminescent materials, 2,3,6,7,10,11-hexacyano-1,4,5,8,9,12-hexaazatriphenylene, 4,4',4'-tri(N-3-methylphenyl-N-phenylamino)triphenylamine, poly[(9,9'-dioctylfluorene-2,7-diyl)-co-(4,4'-(N-(4-sec-butyl)- phenyl) diphenylamine))], poly(4-butylphenyl-diphenylamine) (poly-TPD), poly[bis(4-phenyl)(4-butylphenyl)amine], polyaniline, polypyrrole, poly(p-phenylene vinylene), poly(phenylene vinylene), poly[2-methoxy-5-(2-ethylhexyloxy)-1,4-phenylene vinylene] and poly[2-methoxy-5-(3',7'-dimethyloctyloxy)-1,4-phenylene vinylene], copper phthalocyanine, aromatic tertiary amines, polynuclear aromatic tertiary amines, 4,4'-bis(p-carbazolyl)-1,1'-biphenyl compounds, N,N,N',N'-tetraaryl At least one of benzidine, PEDOT, PEDOT:PSS and its derivatives, PEDOT:PSS derivatives doped with s-MoO3, poly(N-vinylcarbazole) (PVK) and its derivatives, polymethacrylate and its derivatives, poly(9,9-octylfluorene) and its derivatives, poly(spirofluorene) and its derivatives, N,N'-di(naphthalene-1-yl)-N,N'-diphenylbenzidine, spiro NPB, nano-polycrystalline diamond, microcrystalline cellulose, tetracyanoquinodimethane, doped graphene, undoped graphene, C60, transition metal oxides, transition metal sulfides, and transition metal tin compounds.

[0049] The present application provides a display device, which includes the above-mentioned optoelectronic device.

[0050] The present invention has the following beneficial effects:

[0051] The composite conductive film of the present invention is provided with a protective layer, which has high stability and corrosion resistance and effectively protects the conductive layer from being corroded by the external environment such as water and oxygen. BRIEF DESCRIPTION OF THE DRAWINGS

[0052] Figure 1 is a schematic diagram of the structure of an electrode provided by an embodiment of the present invention;

[0053] Figure 2 is a flow chart of the method for preparing the electrode structure of the present invention;

[0054] Figure 3 is a schematic structural diagram of an optoelectronic device provided by an embodiment of the present invention;

[0055] Among them, 10, composite conductive film; 11, protective layer; 12, conductive layer; 100, optoelectronic device; 20, anode; 30, hole injection layer; 40, hole transport layer; 50, light-emitting layer; 60, electron transport layer. DETAILED DESCRIPTION

[0056] The present invention will be further described below in conjunction with specific embodiments.

[0057] The technical solutions in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without making creative work belong to the scope of protection of the present application. In addition, it should be understood that the specific implementation methods described herein are only used to illustrate and explain the present application, and are not used to limit the present application.

[0058] In this application, unless otherwise stated, directional words such as "upper" and "lower" generally refer to the upper and lower parts of the device in actual use or working state, specifically the drawing direction in the accompanying drawings; while "inner" and "outer" refer to the outline of the device. In addition, in the description of this application, the term "including" means "including but not limited to". The terms first, second, third, etc. are used only as labels and do not impose numerical requirements or establish an order.

[0059] In this application, "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural.

[0060] In the present application, "at least one" means one or more, and "plurality" means two or more. "At least one", "at least one of the following" or similar expressions refer to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.

[0061] In the present application, when a layer is formed "on" another layer, the so-called "on" is a broad concept, which may indicate that the formed another layer is adjacent to the certain layer, or may indicate that there are other spacing structural layers between the another layer and the certain layer. For example, when a second electrode is formed "on" the first carrier functional layer, the so-called "on" may indicate that the formed second electrode is adjacent to the first carrier functional layer, or may indicate that there are other spacing structural layers between the second electrode and the first carrier functional layer, such as a light-emitting layer.

[0062] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present application; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values ​​within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.

[0063] In optoelectronic devices such as QLED devices, the electrodes are prone to oxidation and corrosion, which leads to degradation of device performance and shortened life. The present application provides a material with good corrosion resistance and protective effect as a protective layer to protect the electrodes from erosion by external environment such as water and oxygen. The technical solution of the present application is as follows:

[0064] First, see Figure 1 An embodiment of the present application provides a composite conductive film 10, including a conductive layer 12, and a protective layer 11 provided on at least one surface thereof; the material of the protective layer 11 includes a material having a hydrophilic group and a hydrophobic group; or the material of the protective layer 11 includes a material having a polar group and a non-polar group.

[0065] It can be understood that the protective layer is arranged on the surface of the conductive layer, which can effectively protect the electrode from oxidation and corrosion by water and oxygen. At the same time, the molecules of the protective layer material have interaction forces, which can enable it to self-assemble into a stable film structure, thereby improving the bonding force with the conductive layer and thus improving the stability of the conductive film.

[0066] In some embodiments, at least one surface of the conductive layer 12 has hydroxyl groups, and the protective layer 11 is disposed on the surface of the conductive layer 12 having hydroxyl groups; and / or

[0067] At least part of the hydroxyl groups on the surface of the conductive layer 12 are connected to the hydrophilic groups through chemical bonds; and / or

[0068] The thickness ratio of the protective layer to the conductive layer 12 is (10-30):(80-120).

[0069] In some embodiments, the material having a hydrophilic group and a hydrophobic group comprises a surfactant; and / or

[0070] The material of the protective layer 11 includes a surfactant and an oxidant; and / or

[0071] The volume ratio of the oxidant to the surfactant is 1:(1-3).

[0072] Since the surface of the conductive layer has hydroxyl groups, a hydroxylated conductive layer surface is formed, and the protective layer has hydrophilic groups, the hydroxyl groups on the surface of the conductive layer and the hydrophilic groups of the protective layer are connected through chemical bonds, so that the self-assembled protective layer is tightly attached to the electrode surface and will not fall off.

[0073] It is understandable that the hydrophilic oxidant can oxidize the impurities and oxides on the electrode surface, making the electrode surface smoother and cleaner, while the hydrophilic group and the hydroxylated electrode surface contact to form a stronger interaction, so that the self-assembled protective layer is tightly attached to the electrode surface and will not fall off; on the other hand, the hydrophilic and hydrophobic groups of the protective layer are used to make the hydrophilic group and the hydroxylated electrode surface interact with each other, and the hydrophobic group is at the outermost side of the device to block the erosion of external water. Therefore, the self-assembled protective layer described in the present application has the effect of corrosion resistance and oxidation resistance, can effectively protect the electrode, improve the corrosion resistance and oxidation resistance of the electrode, and improve the long-term stability of the electrode.

[0074] In some embodiments, ferric sulfate and hexadecyltrimethylammonium bromide are combined in a volume ratio of 1:(1-3), wherein ferric sulfate is a hydrophilic oxidant that can oxidize impurities and oxides on the surface of the conductive layer, making the surface of the conductive layer smoother and cleaner, while sulfate ions and iron ions are hydrophilic, and hexadecyltrimethylammonium bromide is a cationic surfactant having hydrophilic and hydrophobic groups, and the hydrophilic and hydrophobic groups contained therein interact with the hydroxyl groups on the electrode surface to form a layer of stable and orderly molecular self-assembled film (SAM), which can form a protective layer on the electrode surface, thereby having anti-corrosion and anti-oxidation effects. In addition, the molecular size and shape of ferric sulfate and hexadecyltrimethylammonium bromide match the surface of the silver electrode, which is also conducive to the formation of the self-assembled film.

[0075] In some embodiments, the polar group comprises an ester group; and / or the non-polar group comprises at least one of an alkenyl group, an alkyl group, and a phenyl group; and / or

[0076] The material having polar groups and non-polar groups includes at least one of diethyl maleate, vinyl acetate, methyl acrylate, ethyl acrylate, methyl methacrylate, styrene, methyl methacrylate, and ethyl methacrylate; and / or

[0077] The material of the protective layer is any of the following:

[0078] (a) the material of the protective layer includes diethyl maleate and vinyl acetate, and the volume ratio of diethyl maleate to vinyl acetate is 1:(1-3);

[0079] (b) the material of the protective layer includes methyl acrylate and ethyl acrylate, and the volume ratio of methyl acrylate to ethyl acrylate is 1:(1-3);

[0080] (c) the material of the protective layer includes methyl methacrylate and styrene, and the volume ratio of methyl methacrylate to styrene is 1:(1-3);

[0081] (d) The material of the protective layer includes methyl methacrylate and ethyl methacrylate, and the volume ratio of methyl methacrylate to ethyl methacrylate is 1:(1-3).

[0082] In some embodiments, vinyl acetate and diethyl maleate are combined in a volume ratio of 1:(1-3), and self-assembly is achieved by forming van der Waals forces through polar groups and non-polar groups in the vinyl acetate and diethyl maleate molecules, wherein the polar group is the ester group (-COO-), and the non-polar group is the olefin group (-CH=CH2, -C=C-). Similarly, self-assembly is achieved by forming van der Waals forces through polar groups and non-polar groups, including the combination of methyl acrylate and ethyl acrylate, which has a polar ester group and a non-polar alkyl group; the combination of methyl methacrylate and styrene, which has a polar ester group and a non-polar aromatic group; and the combination of methyl methacrylate and ethyl methacrylate, which has a polar ester group and a non-polar alkyl group. Furthermore, the intermolecular interaction forces in the self-assembled layer may also include hydrogen bonds, electrostatic interactions, etc. These interaction forces can cause the molecules to self-assemble into a stable film structure, so that the protective layer prepared in the present application remains on the surface of the electrode conductive layer for a long time.

[0083] The material of the electrode includes, but is not limited to, a doped metal oxide particle electrode, a composite electrode, a graphene electrode, a carbon nanotube electrode, a metal single substance electrode or an alloy electrode. The material of the doped metal oxide particle electrode may include, but is not limited to, one or more of indium doped tin oxide (ITO), fluorine doped tin oxide (FTO), antimony doped tin oxide (ATO), aluminum doped zinc oxide (AZO), gallium doped zinc oxide (GZO), indium doped zinc oxide (IZO), magnesium doped zinc oxide (MZO) and aluminum doped magnesium oxide (AMO). The composite electrode is a composite electrode in which metal is sandwiched between doped or undoped transparent metal oxide particles, such as AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, TiO2 / Ag / TiO2, TiO2 / Al / TiO2, ZnS / Ag / ZnS, ZnS / Al / ZnS, etc., wherein " / " represents a stacked structure, for example, AZO / Ag / AZO represents a composite electrode including an AZO layer, an Ag layer and an AZO layer stacked in sequence. The material of the metal single substance electrode may include but is not limited to one or more of Ag, Al, Cu, Mo, Au, Pt, Ca, Mg and Ba.

[0084] The ratio of the thickness of the protective layer to the conductive layer is (10-30): (80-120); further, the thickness of the electrode layer can range from 80 to 120 nm; for example, 80 nm, 90 nm, 100 nm, 110 nm, 120 nm; the thickness of the self-assembled protective layer can range from 10 to 30 nm; for example, 10 nm, 20 nm, 30 nm. Within the range of the thickness of the electrode layer and the thickness of the protective layer, the electrode can be effectively protected from corrosion and oxidation, and a strong bonding force between the self-assembled layer and the electrode surface can be ensured, so that the self-assembled layer is not easy to fall off.

[0085] Second, see Figure 2 The present invention also provides a method for preparing a composite conductive film, comprising the following steps:

[0086] Step S11, providing a conductive layer;

[0087] Step S12: providing a protective layer precursor solution, and placing the protective layer precursor on at least one surface of the conductive layer to form a protective layer precursor.

[0088] The precursor solution of the protective layer is obtained by dissolving the protective layer material in an organic solvent.

[0089] Step S12 specifically includes placing a precursor of the protective layer on at least one surface of the conductive layer, and leaving it to stand for 10 to 30 minutes, for example, 10 minutes, 20 minutes, or 30 minutes, to form the precursor of the protective layer.

[0090] Step S13, heating the protective layer precursor to obtain a protective layer.

[0091] Specifically, the protective layer precursor is heated at 50-70°C for 5-20 minutes; for example, the temperature is 50°C, 60°C, 70°C; the heating time is 5 minutes, 10 minutes, 15 minutes, 20 minutes. Within the temperature and time range of the heat treatment, the formation of the self-assembled protective layer film is favorable.

[0092] The hydrophilic groups of the protective layer of the present invention can form a stable interaction force with the surface hydroxyl groups of the conductive layer after hydroxylation treatment, thereby increasing the bonding force between the protective layer and the surface of the conductive layer, while the hydrophobic groups are on the outermost side of the device to block the erosion of external water, thereby improving the stability and corrosion resistance of the composite conductive film.

[0093] In some embodiments, in step S12:

[0094] The protective layer material includes a surfactant, or includes a surfactant and an oxidant, wherein the volume ratio of the oxidant to the surfactant is 1:(1-3).

[0095] In some embodiments, the oxidant comprises a hydrophilic oxidant, and the hydrophilic oxidant comprises one or more of ferric sulfate and copper sulfate;

[0096] The surfactant includes one or more of cetyltrimethylammonium bromide, cetyltrimethylammonium chloride, and sodium dodecyl sulfate.

[0097] In some embodiments, the material of the protective layer includes ferric sulfate and hexadecyltrimethylammonium bromide, vinyl acetate and diethyl maleate or copper sulfate and hexadecyltrimethylammonium bromide mixed in a volume ratio of 1:(1-3); for example, a volume ratio of 1:1, 1:2, 1:3. Within the volume ratio range, the self-assembly reaction in the protective layer is conducive to proceed.

[0098] In some embodiments, in step S12:

[0099] The protective layer material includes at least one of diethyl maleate, vinyl acetate, methyl acrylate, ethyl acrylate, methyl methacrylate, styrene, methyl methacrylate, and ethyl methacrylate.

[0100] In some embodiments, the material of the protective layer is any of the following:

[0101] (a) the material of the protective layer includes diethyl maleate and vinyl acetate, and the volume ratio of diethyl maleate to vinyl acetate is 1:(1-3);

[0102] (b) the material of the protective layer includes methyl acrylate and ethyl acrylate, and the volume ratio of methyl acrylate to ethyl acrylate is 1:(1-3);

[0103] (c) the material of the protective layer includes methyl methacrylate and styrene, and the volume ratio of methyl methacrylate to styrene is 1:(1-3);

[0104] (d) The material of the protective layer includes methyl methacrylate and ethyl methacrylate, and the volume ratio of methyl methacrylate to ethyl methacrylate is 1:(1-3).

[0105] By mixing two materials having polar groups and non-polar groups in a volume ratio of 1:(1-3), such as a volume ratio of 1:1, 1:2, 1:3, the self-assembly reaction in the protective layer is facilitated.

[0106] In the precursor solution of the protective layer, the concentration of the protective layer material is 0.05-0.1 M, for example, 0.05 M, 0.06 M, 0.07 M, 0.075 M, 0.08 M, 0.09 M, 0.1 M. Within the concentration range, it is conducive to forming a stronger interaction, so that the self-assembled protective layer is not easy to fall off.

[0107] The organic solvent includes alcohol solvents, chloroform, chlorobenzene, toluene; wherein the alcohol solvent includes one or more of ethanol, propanol, butanol, and pentanol.

[0108] In some embodiments, in step S12:

[0109] Before the precursor solution of the self-assembled protective layer is dripped onto the surface of the conductive layer, the process also includes: performing hydroxylation treatment on at least one surface of the conductive layer, using an acidic cleaning solution and standing for 20 to 40 minutes to acid-wash the surface of the conductive layer, removing oxides and organic matter on the surface, and forming hydroxyl functional groups, and the precursor solution of the protective layer is set onto the surface of the conductive layer having hydroxyl groups.

[0110] In some embodiments, the acidic cleaning solution includes concentrated acid, which includes but is not limited to concentrated nitric acid, concentrated sulfuric acid, concentrated hydrochloric acid, and the like.

[0111] In some embodiments, the concentration of the concentrated acid ranges from 1.6 to 4 g / ml, for example, 1.6 g / ml, 1.8 g / ml, 2 g / ml, 2.2 g / ml, 2.4 g / ml, 2.6 g / ml, 2.8 g / ml, 3 g / ml, 3.2 g / ml, 3.4 g / ml, 3.6 g / ml, 3.8 g / ml, and 4 g / ml. Within the concentration range, oxides and organic matter on the electrode surface can be fully removed, and hydroxyl functional groups can be formed.

[0112] In some embodiments, in step S13:

[0113] The drying method includes blowing out the residual solution on the surface of the electrode with nitrogen.

[0114] Third, see Figure 3 The embodiment of the present application further provides a photoelectric device 100, comprising a bottom electrode 20, a light-emitting layer 50 and a top electrode stacked in sequence; the top electrode comprises the composite conductive film 10 described in the present application.

[0115] The optoelectronic device includes a hole transport layer 40 between the bottom electrode and the light-emitting layer;

[0116] The optoelectronic device further includes a hole injection layer 30 between the bottom electrode 20 and the hole transport layer.

[0117] The optoelectronic device includes an electron transport layer 60 between the light emitting layer 50 and the composite conductive film 10 .

[0118] The material of the hole transport layer can also be a material known in the art for a hole transport layer, including but not limited to 4,4'-N,N'-dicarbazolyl-biphenyl (CBP), poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine] (PTAA), N,N'-diphenyl-N,N'-bis(1-naphthyl)-1,1'-biphenyl-4,4"-diamine (α-NPD), N,N'-diphenyl-N,N'-bis(3-methylphenyl)-(1,1'-biphenyl)-4,4'-diamine (TPD), poly(N,N'-bis(4-butylphenyl)-N,N'-bis(phenyl)benzidine) (Poly-TPD), N,N'-bis(3-methylphenyl)-(1,1'-biphenyl)-4,4'-diamine (TPD). phenyl)-N,N'-bis(phenyl)-spiro(spiro-TPD), N,N'-bis(4-(N,N'-diphenyl-amino)phenyl)-N,N'-diphenylbenzidine (DNTPD), 4,4',4'-tri(N-carbazolyl)-triphenylamine (TCTA), 4,4',4'-tri(N-3-methylphenyl-N-phenylamino)triphenylamine (m-MTDATA), poly[(9,9'-dioctylfluorene-2,7-diyl)-co-(4,4'-(N-(4-sec-butylphenyl)diphenylamine))] (TFB), poly(N-vinylcarbazole) (PVK) and its derivatives, N,N'-di(1-naphthyl)-N,N'-diphenyl-1, 1'-Biphenyl-4-4'-diamine (NPB), spiro NPB, poly(phenylene vinylene) (PPV), poly[2-methoxy-5-(2-ethylhexyloxy)-1,4-phenylene vinylene] (MEH-PPV), poly[2-methoxy-5-(3',7'-dimethyloctyloxy)-1,4-phenylene vinylene] (MOMO-PPV), 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene (spiro-omeTAD), 4,4'-cyclohexylbis[N,N-di(4-methylphenyl)aniline] (TAPC), 1,3-bis(carbazol-9-yl)benzene (MCP) , polyaniline, polypyrrole, poly(p-)phenylene vinylene, aromatic tertiary amine, polynuclear aromatic tertiary amine, 4,4'-bis(p-carbazolyl)-1,1'-biphenyl compound, N,N,N',N'-tetraarylbenzidine, PEDOT:PSS and its derivatives, polymethacrylate and its derivatives, poly(9,9-octylfluorene) and its derivatives, poly(spirofluorene) and its derivatives, doped graphene, undoped graphene, C60, doped or undoped NiO, doped or undoped MoO3, doped or undoped WO3, doped or undoped V2O5, doped or undoped P-type gallium nitride, doped or undoped CrO3, doped or undoped CuO. One or more.

[0119] The material of the electron transport layer is a material known in the art for the electron transport layer, including but not limited to one or more of inorganic electron transport materials and organic electron transport materials. The inorganic electron transport material includes one or more of doped or undoped zinc oxide, barium oxide, titanium oxide, tin oxide, tantalum oxide, zirconium oxide, cadmium sulfide, zinc sulfide, zinc tin, indium phosphide, gallium phosphide, and barium titanate, wherein the doped element includes one or more of aluminum, magnesium, lithium, manganese, yttrium, lanthanum, copper, nickel, zirconium, cerium, and gadolinium. The organic electron transport material includes one or more of quinoxaline compounds, imidazole compounds, triazine compounds, fluorene-containing compounds, and hydroxyquinoline compounds.

[0120] The material of the hole injection layer can be a material known in the art for the hole injection layer, for example, it can be selected from but not limited to 2,3,6,7,10,11-hexacyano-1,4,5,8,9,12-hexaazatriphenylene (HAT-CN), PEDOT, PEDOT:PSS, a derivative of PEDOT:PSS doped with s-MoO3 (PEDOT:PSS:s-MoO3), 4,4',4'-tris(N-3-methylphenyl-N-phenylamino)triphenylamine (m-MTDATA), tetracyanoquinodimethane (F4-TCQN), copper phthalocyanine, nickel oxide, molybdenum oxide, tungsten oxide, vanadium oxide, molybdenum sulfide, tungsten sulfide and copper oxide. One or more.

[0121] The material of the light-emitting layer may include, but is not limited to, one or more quantum dot light-emitting materials, and may also include organic light-emitting materials.

[0122] That is, the quantum dot light-emitting material in the quantum dot layer may include, but is not limited to, one or more of single structure quantum dots, core-shell structure quantum dots and perovskite semiconductor materials.

[0123] The material of the single structure quantum dots, the core material of the core-shell structure quantum dots and the shell material of the core-shell structure quantum dots may respectively include but are not limited to one or more of II-VI group compounds, IV-VI group compounds, III-V group compounds and I-III-VI group compounds. The II-VI group compounds may include, but are not limited to, one or more of CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, CdSeS, CdSeTe, CdSTe, ZnSeS, ZnSeTe, ZnSTe, HgSeS, HgSeTe, HgSTe, CdZnS, CdZnSe, CdZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe and HgZnSTe. The IV-VI group compounds may include, but are not limited to, one or more of SnS, SnSe, SnTe, PbS, PbSe, PbTe, SnSeS, SnSeTe, SnSTe, PbSeS, PbSeTe, PbSTe, SnPbS, SnPbSe, SnPbTe, SnPbSSe, SnPbSeTe, and SnPbSTe. The III-V group compound may include, but is not limited to, one or more of GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, GaNP, GaNAs, GaNSb, GaPAs, GaPSb, AlNP, AlNAs, AlNSb, AlPAs, AlPSb, InNP, InNAs, InNSb, InPAs, InPSb, GaAlNP, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInNP, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs, and InAlPSb. The I-III-VI group compound may include, but is not limited to, one or more of CuInS2, CuInSe2, and AgInS2.

[0124] As an example, the core-shell structured quantum dots may include, but are not limited to, one or more of CdSe / CdSeS / CdS, InP / ZnSeS / ZnS, CdZnSe / ZnSe / ZnS, CdSeS / ZnSeS / ZnS, CdSe / ZnS, CdSe / ZnSe / ZnS, ZnSe / ZnS, ZnSeTe / ZnS, CdSe / CdZnSeS / ZnS and InP / ZnSe / ZnS.

[0125] The organic light-emitting material may include, but is not limited to, one or more of CBP:Ir(mppy)3(4,4'-bis(N-carbazole)-1,1'-biphenyl:tri[2-(p-tolyl)pyridine iridium(III)), TCTX:Ir(mmpy)(4,4',4"-tri(carbazole-9-yl)triphenylamine:tri[2-(p-tolyl)pyridine iridium), diaromatic anthracene derivatives, distilbene aromatic derivatives, pyrene derivatives, fluorene derivatives, TBPe fluorescent materials, TTPX fluorescent materials, TBRb fluorescent materials, DBP fluorescent materials, delayed fluorescent materials, TTA materials, TADF (thermally activated delay) materials, polymers containing covalent bonds of BN, HLCT (hybridized localized charge transfer excited state) materials, Exciplex (exciplex) light-emitting materials, polyacetylene and its derivatives, polyparaphenylene and its derivatives, polythiophene and its derivatives, polyfluorene and its derivatives.

[0126] It is understandable that the optoelectronic device may also be provided with some functional layers conventionally used in optoelectronic devices that help improve the performance of the optoelectronic device, such as an electron blocking layer, a hole blocking layer, an electron injection layer, an interface modification layer, and the like.

[0127] It can be understood that the materials of each layer of the optoelectronic device can be adjusted according to the light emitting requirements of the optoelectronic device.

[0128] In some embodiments, the optoelectronic device further includes a substrate, and the substrate is disposed on a side of the bottom electrode away from the light-emitting layer, or the substrate is disposed on a side of the top electrode away from the light-emitting layer.

[0129] The substrate may be a rigid substrate or a flexible substrate. In some embodiments, the material of the substrate may include but is not limited to one or more of glass, silicon wafer, polycarbonate, polymethyl methacrylate, polyethylene terephthalate, polyethylene naphthalate, polyamide and polyether sulfone.

[0130] It is understood that the optoelectronic device may be an upright optoelectronic device or an inverted optoelectronic device. The optoelectronic device may be a quantum dot optoelectronic device or an organic optoelectronic device.

[0131] The cathode of the photoelectric device includes the electrode structure described in the present application, thereby having higher stability and longer lifespan.

[0132] In a fourth aspect, the present application also provides a method for preparing a photoelectric device, comprising the following steps:

[0133] Providing a photoelectric device preform; the photoelectric device preform includes a substrate, or includes a bottom electrode and a plurality of functional layers located on the bottom electrode, wherein the plurality of functional layers includes a light-emitting layer;

[0134] When the optoelectronic device preform includes a substrate, a bottom electrode is prepared on the surface of the substrate, and after the functional layer is prepared on the surface of the bottom electrode, a top electrode is prepared on the surface of the functional layer, and at least one of the bottom electrode and the top electrode is the composite conductive film or is prepared by the composite conductive film preparation method; or

[0135] When the optoelectronic device preform includes a bottom electrode and several functional layers located on the bottom electrode, a top electrode is prepared on the functional layers, and the top electrode is the composite conductive film or is prepared by the composite conductive film preparation method.

[0136] The functional layer includes a hole functional layer and an electron functional layer, the hole functional layer includes a hole transport layer and a hole injection layer, and the electron functional layer includes an electron transport layer;

[0137] providing a hole transport layer between the bottom electrode and the light emitting layer;

[0138] providing a hole injection layer between the bottom electrode and the hole transport layer;

[0139] An electron transport layer is provided between the light emitting layer and the top electrode.

[0140] The photoelectric device is an upright device; or, the photoelectric device is an inverted device; that is, the bottom electrode is configured as an anode and the top electrode is configured as a cathode; or, the bottom electrode is configured as a cathode and the top electrode is configured as an anode.

[0141] Correspondingly, the present application also provides a display device, which includes the above-mentioned optoelectronic device.

[0142] The display device can be any electronic product with a display function, including but not limited to smart phones, tablet computers, laptops, digital cameras, digital video cameras, smart wearable devices, smart weighing electronic scales, car displays, televisions or e-book readers, among which smart wearable devices can be, for example, smart bracelets, smart watches, virtual reality (VR) helmets, etc.

[0143] Film Example 1

[0144] The process of preparing the composite conductive film is as follows:

[0145] Step 1: Acid cleaning, using concentrated sulfuric acid with a concentration of 2g / ml as an acid cleaning solution to clean the surface of the silver electrode of the conductive layer, remove surface oxides and organic matter, etc., expose the bare part of the silver surface, and form hydroxyl functional groups.

[0146] Step 2: Dissolve ferric sulfate in ethanol to obtain a 0.075M ferric sulfate solution, dissolve hexadecyltrimethylammonium bromide in chloroform to a solution concentration of 0.075mM, and mix the two solutions in a volume ratio of 1:1 to obtain a protective layer precursor solution.

[0147] Step 3: Add the obtained protective layer precursor solution dropwise onto the surface of the silver electrode and let it stand for 10 minutes.

[0148] Step 4: Drying: Use nitrogen to blow dry the residual solution on the surface of the silver electrode and heat it at 60°C for 10 minutes.

[0149] Film Example 2

[0150] This embodiment is substantially the same as the thin film embodiment 1, except that this embodiment uses 0.075 M copper sulfate (CuSO 4 ) and 0.075 mM hexadecyltrimethylammonium bromide (CTAB) as the precursor solution of the self-assembly layer.

[0151] Film Example 3

[0152] This embodiment is basically the same as the thin film embodiment 1, except that this embodiment uses aluminum as the electrode material.

[0153] Film Example 4

[0154] This embodiment is basically the same as the thin film embodiment 1, except that this embodiment uses a silver-copper alloy electrode as the electrode material.

[0155] Film Example 5

[0156] This embodiment is basically the same as the thin film embodiment 1, except that this embodiment uses silver oxide metal oxide electrode as the electrode material.

[0157] Film Example 6

[0158] This embodiment is basically the same as the film embodiment 1, except that the concentration of ferric sulfate in the self-assembled layer of this embodiment is 0.05 M, and the concentration of hexadecyltrimethylammonium bromide is 0.05 mM.

[0159] Film Example 7

[0160] This embodiment is substantially the same as the film embodiment 1, except that the concentration of ferric sulfate in the self-assembled layer of this embodiment is 0.1 M, and the concentration of hexadecyltrimethylammonium bromide is 0.1 mM.

[0161] Film Example 8

[0162] This embodiment is basically the same as the film embodiment 1, except that the heat treatment temperature in this embodiment is 50°C.

[0163] Film Example 9

[0164] This embodiment is basically the same as the film embodiment 1, except that the heat treatment temperature in this embodiment is 70°C.

[0165] Film Example 10

[0166] This embodiment is basically the same as the film embodiment 1, except that the heat treatment time in this embodiment is 5 minutes.

[0167] Film Example 11

[0168] This embodiment is basically the same as the film embodiment 1, except that the heat treatment time in this embodiment is 20 minutes.

[0169] Film Example 12

[0170] This embodiment is basically the same as the film embodiment 1, except that the concentration of concentrated sulfuric acid used in the acid cleaning in this embodiment is 1.6 g / ml.

[0171] Film Example 13

[0172] This embodiment is basically the same as the film embodiment 1, except that the concentration of concentrated sulfuric acid used in the acid cleaning in this embodiment is 4 g / ml.

[0173] Film Example 14

[0174] This embodiment is basically the same as the thin film embodiment 1, except that the materials of the self-assembled electrode protective layer in this embodiment are vinyl acetate and diethyl maleate.

[0175] Film Comparative Example 1

[0176] This comparative example is substantially the same as the thin film example 1, except that no protective layer is provided on the surface of the silver electrode in this comparative example.

[0177] Film Comparative Example 2

[0178] This comparative example is basically the same as the film example 1, except that this comparative example does not use concentrated acid to perform hydroxylation treatment on the surface of the silver electrode.

[0179] Film Comparative Example 3

[0180] This comparative example is substantially the same as film example 1, except that vinyl acetate is used as the material of the protective layer in this comparative example.

[0181] The film examples 1 to 14 and the film comparison examples 1 to 3 were tested for corrosion resistance, conductivity stability, and the bonding strength between the self-assembled layer and the electrode surface. The test results are shown in Table 1.

[0182] The test method for corrosion resistance and conductive stability is: placing the electrodes prepared from the film embodiments 1 to 14 of the present application and the film comparison examples 1, 2, and 3 in a humid environment with an air humidity of 80% for 3 days, and observing the rust condition and conductivity of the electrode surface.

[0183] The test method for the bonding strength between the self-assembled protective layer and the electrode surface is the scratch method: use a hard steel knife that has been ground to a 30° angle to draw two parallel lines about 2 mm apart on the electrode surface. When scratching, sufficient pressure should be applied to make a single stroke through the self-assembled layer and cut to the underlying metal. Observe the coating with the naked eye or a 4-5x magnifying glass. If it does not peel or fall off, the bonding strength is strong.

[0184] Table 1. Statistical table of composite conductive film properties prepared from various film embodiments and film comparison examples of the present invention

[0185]

[0186] The conductivity change rate in Table 1 is the ratio of the conductivity before the test minus the conductivity after the test divided by the conductivity before the test.

[0187] As can be seen from Table 1, compared with the film comparative example 1, the film embodiments 1 to 14 have a lower conductivity change rate. It can be seen that the self-assembled electrode protection layer of the present application effectively improves the stability of the electrode, while the electrode of comparative example 1 is obviously corroded, and the conductivity decreases by about 50%. The reason may be that the hydrophobic groups in the self-assembled electrode protection layer set in the film embodiments 1 to 14 of the present application are on the outermost side of the device, blocking the erosion of external water, thereby improving the stability and corrosion resistance of the electrode, and effectively protecting the photoelectric device electrode from erosion by the external environment such as water and oxygen.

[0188] Compared with the film comparative example 2, the optoelectronic devices of the film embodiments 1 to 14 had no peeling phenomenon, while the comparative example 2 produced obvious stratification and peeling. It can be seen that the binding force between the self-assembled layer and the electrode surface in the present application is effectively improved. The reason may be that the embodiment of the present application uses an acidic solution to clean the silver electrode surface, removes surface impurities and forms hydroxyl functional groups at the same time, which is not only more conducive to the binding of the self-assembled layer to the electrode surface, but also allows the hydrophilic groups of the self-assembled layer to interact with the hydroxyl groups on the surface of the silver electrode to form stable chemical bonds, thereby further increasing the binding force between the self-assembled layer and the electrode surface.

[0189] On the other hand, although the film comparison example 3 uses a single protective layer material and shows the same bonding ability as the combined material, its conductivity change rate is larger and its stability is weaker. This shows that the two materials of the present application must be combined in a certain proportion to produce better technical effects.

[0190] The film examples 1 to 14 prepared in the present application showed no peeling phenomenon after the binding force test, the conductivity change rate was low, and the stability was greatly improved; at the same time, the heating temperature and time during the heat treatment can effectively enhance the formation of the self-assembled film. The photoelectric device electrode prepared in this way has better corrosion resistance and stability.

[0191] Device Example 1

[0192] After completing the preparation steps of a 25 nm thick PEOT:PSS hole injection layer, a 25 nm thick TFB hole transport layer, a 30 nm thick CdZnSe quantum dot layer, a 30 nm thick ZnO electron transport layer, and a silver electrode in the QLED device on ITO, the preparation of the self-assembled electrode protection layer in this application is carried out.

[0193] The process of preparing the self-assembled electrode protective layer is as follows:

[0194] Step 1: Use concentrated sulfuric acid with a concentration of 2g / ml as an acidic cleaning solution to clean the surface of the silver electrode, remove surface oxides and organic matter, expose the bare part of the silver surface, and form hydroxyl functional groups.

[0195] Step 2: Dissolve ferric sulfate in ethanol to obtain a 0.075M ferric sulfate solution, dissolve hexadecyltrimethylammonium bromide in chloroform to obtain a solution concentration of 0.075mM, and mix the two solutions in a volume ratio of 1:1.

[0196] Step 3: Add the self-assembly solution dropwise onto the surface of the silver electrode and let stand for 10 minutes.

[0197] Step 4: Drying: Use nitrogen to blow dry the residual solution on the surface of the silver electrode and heat it at 60°C for 10 minutes.

[0198] Finally, packaging is performed.

[0199] The hydrophilic groups of the self-assembled electrode protection layer can interact with the surface hydroxyl groups of the hydroxylated silver electrode surface, thereby increasing the binding force between the self-assembled electrode protection layer and the electrode surface and improving the stability and corrosion resistance of the electrode.

[0200] Device Examples 2 to 14

[0201] The preparation methods of device embodiments 2 to 14 are basically the same as those of device embodiment 1, except that device embodiments 2 to 15 respectively adopt the preparation methods of the composite conductive thin films in thin film embodiments 2 to 14 to form electrodes.

[0202] Device Comparative Example 1

[0203] This comparative example is basically the same as device embodiment 1, except that the electrode is formed by using the preparation method of the composite conductive film in thin film comparative example 1.

[0204] Device Comparison Example 2

[0205] This comparative example is basically the same as device embodiment 1, except that the electrode is formed by using the preparation method of the composite conductive film in thin film comparative example 2.

[0206] Device Comparison Example 3

[0207] This comparative example is basically the same as device embodiment 1, except that the electrode is formed by using the preparation method of the composite conductive film in thin film comparative example 3.

[0208] The device embodiments 1 to 14 and the device comparative examples 1 to 3 were subjected to a lifespan T95@1000nit test. The test results are shown in Table 2.

[0209] The test method for life span T95@1000nit is: in CDA gas, under constant current or voltage drive, measure the time taken for the device brightness to decay to a certain proportion of the maximum brightness, and the time taken for the brightness to decay to 95% of the maximum brightness is defined as T95, and this life span is the measured life span. In order to shorten the life span test cycle, the device life span test is usually carried out at high brightness by accelerating device aging, and the life span at low brightness is obtained by fitting the decay fitting formula. For example, the life span at 1000nits is recorded as T95@1000nits, and the calculation formula is:

[0210]

[0211] Among them, T95 L The lifespan under low brightness, generally 1000nits, T95 H is the lifespan under high brightness, that is, the measured lifespan, L H is the maximum brightness that the device is accelerated to, L L Generally, it is 1000nits, A is the acceleration factor, which is 1.7. The constant current is 2mA.

[0212] Table 2. Performance statistics of optoelectronic devices prepared from various device embodiments and device comparison examples of the present invention

[0213]

[0214]

[0215] It can be seen from Table 2 that compared with device comparison examples 1 to 3, device embodiments 1 to 14 have stronger electrode bonding force, no peeling phenomenon, and greatly improved stability, and the electrode life is greatly improved, so that the life of the optoelectronic device is also greatly improved.

[0216] Device Comparative Example 3 uses a single conductive layer material, which has a shorter electrode life and poorer protection capability than the combined materials used in device Examples 1 to 14.

[0217] The technical solutions provided by the embodiments of the present application are introduced in detail above. Specific examples are used herein to illustrate the principles and implementation methods of the present application. The description of the above embodiments is only used to help understand the method of the present application and its core idea. At the same time, for technical personnel in this field, according to the idea of ​​the present application, there will be changes in the specific implementation methods and application scope. In summary, the content of this specification should not be understood as a limitation on the present application.

Claims

1. A composite conductive film, characterized in that: It comprises a conductive layer and a protective layer disposed on at least one surface thereof; the material of the protective layer comprises a material having a hydrophilic group and a hydrophobic group; or The material of the protective layer includes a material having a polar group and a non-polar group.

2. The composite conductive film according to claim 1, characterized in that: The material having a hydrophilic group and a hydrophobic group includes a surfactant; and / or The material of the protective layer includes a surfactant and an oxidant; and / or The volume ratio of the oxidant to the surfactant is 1:(1-3).

3. The composite conductive film according to claim 2, characterized in that: The oxidant comprises a hydrophilic oxidant, and the hydrophilic oxidant comprises one or more of ferric sulfate and copper sulfate; and / or The surfactant includes one or more of cetyltrimethylammonium bromide, cetyltrimethylammonium chloride, and sodium dodecyl sulfate.

4. The composite conductive film according to claim 1, characterized in that: The polar group includes an ester group; and / or the non-polar group includes at least one of an alkenyl group, an alkyl group, and a phenyl group; and / or The material having polar groups and non-polar groups includes at least one of diethyl maleate, vinyl acetate, methyl acrylate, ethyl acrylate, methyl methacrylate, styrene, methyl methacrylate, and ethyl methacrylate; and / or The material of the protective layer is any of the following: (a) the material of the protective layer includes diethyl maleate and vinyl acetate, and the volume ratio of diethyl maleate to vinyl acetate is 1:(1-3); (b) the material of the protective layer includes methyl acrylate and ethyl acrylate, and the volume ratio of methyl acrylate to ethyl acrylate is 1:(1-3); (c) the material of the protective layer includes methyl methacrylate and styrene, and the volume ratio of methyl methacrylate to styrene is 1:(1-3); (d) The material of the protective layer includes methyl methacrylate and ethyl methacrylate, and the volume ratio of methyl methacrylate to ethyl methacrylate is 1:(1-3).

5. The composite conductive film according to claim 1, characterized in that: At least one surface of the conductive layer has hydroxyl groups, and the protective layer is disposed on the surface of the conductive layer having hydroxyl groups; and / or At least part of the hydroxyl groups on the surface of the conductive layer are connected to the hydrophilic groups via chemical bonds; and / or The thickness ratio of the protective layer to the conductive layer is (10-30):(80-120).

6. The composite conductive film according to claim 1, characterized in that: The conductive layer includes a doped metal oxide particle electrode, a composite electrode, a graphene electrode, a carbon nanotube electrode, a metal single substance electrode or an alloy electrode. The material of the doped metal oxide particle electrode includes one or more of indium-doped tin oxide, fluorine-doped tin oxide, antimony-doped tin oxide, aluminum-doped zinc oxide, gallium-doped zinc oxide, indium-doped zinc oxide, magnesium-doped zinc oxide and aluminum-doped magnesium oxide. The composite electrode includes one or more of AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, TiO2 / Ag / TiO2, TiO2 / Al / TiO2, ZnS / Ag / ZnS or ZnS / Al / ZnS. The material of the metal single substance electrode includes one or more of Ag, Al, Cu, Mo, Au, Pt, Ca, Mg and Ba.

7. A method for preparing a composite conductive film, characterized in that: The steps include: providing a conductive layer; Providing a protective layer precursor solution, wherein the protective layer precursor solvent includes a protective layer material, the protective layer material includes a material having a hydrophilic group and a hydrophobic group, or the protective layer material includes a material having a polar group and a non-polar group; Disposing the protective layer precursor solution on at least one surface of the conductive layer to form a protective layer precursor; The protective layer precursor is heated to obtain a protective layer.

8. The method for preparing the composite conductive film according to claim 7, characterized in that: The material having a hydrophilic group and a hydrophobic group includes a surfactant; and / or The material of the protective layer includes a surfactant and an oxidant; and / or The volume ratio of the oxidant to the surfactant is 1:(1-3); and / or The oxidant comprises a hydrophilic oxidant, and the hydrophilic oxidant comprises one or more of ferric sulfate and copper sulfate; and / or The surfactant includes one or more of cetyltrimethylammonium bromide, cetyltrimethylammonium chloride, and sodium dodecyl sulfate; and / or The polar group includes an ester group; and / or the non-polar group includes at least one of an alkenyl group, an alkyl group, and a phenyl group; and / or The material having polar groups and non-polar groups includes at least one of diethyl maleate, vinyl acetate, methyl acrylate, ethyl acrylate, methyl methacrylate, styrene, methyl methacrylate, and ethyl methacrylate; and / or The concentration of the protective layer precursor solution is 0.05-0.1M; and / or The heating temperature is 50-70° C. and the heating time is 5-20 min.

9. The method for preparing the composite conductive film according to claim 7, characterized in that: The protective layer precursor solution further comprises an organic solvent, wherein the organic solvent comprises one or more of an alcohol solvent, chloroform, chlorobenzene, and toluene; and / or The alcohol solvent includes one or more of ethanol, propanol, butanol and pentanol.

10. The method for preparing the composite conductive film according to claim 8, characterized in that: At least one surface of the conductive layer has hydroxyl groups, and the protective layer precursor solution is disposed on the surface of the conductive layer having hydroxyl groups; and / or Performing a hydroxylation treatment on at least one surface of the conductive layer so that the surface of the conductive layer has hydroxyl groups; and / or After the protective layer precursor solution is disposed on at least one surface of the conductive layer, the composite conductive film is dried.

11. The method for preparing the composite conductive film according to claim 10, characterized in that: The hydroxylation treatment comprises performing an acid wash treatment on at least one surface of the conductive layer; and / or The pickling treatment comprises placing an acid solution on at least one surface of the conductive layer, leaving it to stand for 20 to 40 minutes, and then cleaning the surface of the conductive layer; and / or The acidic solution includes concentrated acid; the concentration of the concentrated acid is 1.6-4 g / ml, and the concentrated acid includes one or more of concentrated nitric acid, concentrated sulfuric acid, and concentrated hydrochloric acid; and / or The drying process includes providing an inert gas to dry the surface of the composite conductive film; the inert gas includes nitrogen, helium, and argon.

12. A photoelectric device, characterized in that: It comprises a bottom electrode and a top electrode, wherein at least one of the top electrode and the bottom electrode comprises the composite conductive film according to any one of claims 1 to 6, or comprises the composite conductive film prepared by the preparation method according to any one of claims 7 to 11.

13. The optoelectronic device according to claim 13, characterized in that: The photoelectric device further comprises an electronic functional layer disposed between the bottom electrode and the top electrode, the electronic functional layer comprising an electron transport layer and / or an electron injection layer, the materials of the electron transport layer and / or the electron injection layer comprising inorganic materials and / or organic materials respectively; the inorganic material comprises one or more of doped or undoped zinc oxide, barium oxide, nickel oxide, titanium oxide, tin oxide, tantalum oxide, zirconium oxide, nickel oxide, lithium titanium oxide, aluminum zinc oxide, manganese zinc oxide, zinc tin oxide, lithium zinc oxide, indium tin oxide, cadmium sulfide, zinc sulfide, molybdenum sulfide, tungsten sulfide, copper sulfide, zinc tin, indium phosphide, gallium phosphide, copper indium sulfide, copper gallium sulfide, and barium titanate, and the doped element comprises one or more of aluminum, magnesium, lithium, manganese, yttrium, lanthanum, copper, nickel, zirconium, cerium, and gadolinium; the organic material comprises one or more of quinoxaline compounds, imidazole compounds, triazine compounds, fluorene-containing compounds, and hydroxyquinoline compounds; and / or The photoelectric device also includes a light-emitting layer disposed between the bottom electrode and the top electrode, wherein the material of the light-emitting layer includes one or more of an organic light-emitting material and a quantum dot light-emitting material, wherein the organic light-emitting material includes 4,4'-bis(N-carbazole)-1,1'-biphenyl:tri[2-(p-tolyl)pyridine iridium(III), 4,4',4"-tri(carbazole-9-yl)triphenylamine:tri[2-(p-tolyl)pyridine iridium, diaromatic anthracene derivatives, distilbene aromatic derivatives, pyrene derivatives, fluorene derivatives, TBPe fluorescent materials, TTPX fluorescent materials, TBRb fluorescent materials, DBP One or more of fluorescent materials, delayed fluorescent materials, TTA materials, thermally activated delayed materials, polymers containing BN covalent bonds, hybrid localized charge transfer excited state materials, exciplex luminescent materials, polyacetylene and its derivatives, polyparaphenylene and its derivatives, polythiophene and its derivatives, polyfluorene and its derivatives, the quantum dot luminescent materials include one or more of single structure quantum dots, core-shell structure quantum dots and perovskite semiconductor materials, the materials of the single structure quantum dots, the core materials of the core-shell structure quantum dots and the shell materials of the core-shell structure quantum dots include II-VI compounds, IV-VI compounds, respectively. , at least one of a III-V compound and a I-III-VI compound, the II-VI compound comprising CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, CdSeS, CdSeTe, CdSTe, ZnSeS, ZnSeTe, ZnSTe, HgSeS, HgSeTe, HgSTe, CdZnS, CdZnSe, CdZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, Cd at least one of ZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe and HgZnSTe, the IV-VI group compound comprises at least one of SnS, SnSe, SnTe, PbS, PbSe, PbTe, SnSeS, SnSeTe, SnSTe, PbSeS, PbSeTe, PbSTe, SnPbS, SnPbSe, SnPbTe, SnPbSSe, SnPbSeTe and SnPbSTe,The III-V compounds include GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, GaNP, GaNAs, GaNSb, GaPAs, GaPSb, and AlN P, AlNAs, AlNSb, AlPAs, AlPSb, InNP, InNAs, InNSb, InPAs, InPSb, GaAlNP, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInN The compound of Group I-III-VI comprises at least one of CuInS2, CuInSe2 and AgInS2; the perovskite semiconductor material comprises a doped or undoped inorganic perovskite semiconductor, or an organic-inorganic hybrid perovskite semiconductor; the inorganic perovskite semiconductor has a general structural formula of AMX3, wherein A is Cs, + ions, M is a divalent metal cation, including Pb 2+ Sn 2+ , Cu 2+ 、Ni 2+ 、Cd 2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2+ 、Eu 2+ At least one of X is a halogen anion including Cl - Br - ,I - At least one of the following; the general structural formula of the organic-inorganic hybrid perovskite semiconductor is BMX3, wherein B is an organic amine cation, including CH3(CH2) n-2 NH3 + or [NH3(CH2) n NH3] 2+ , where n≥2, M is a divalent metal cation, including Pb 2+ Sn 2+ , Cu 2+ 、Ni 2 + 、Cd 2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2+ 、Eu 2+ At least one of X is a halogen anion including Cl - Br - ,I - At least one of; and / or The photoelectric device further comprises a hole functional layer disposed between the bottom electrode and the top electrode, the hole functional layer comprising a hole transport layer and / or a hole injection layer, the material of the hole transport layer and the material of the hole injection layer respectively and independently comprising 4,4'-N,N'-dicarbazolyl-biphenyl, N,N'-diphenyl-N,N'-bis(1-naphthyl)-1,1'-biphenyl-4,4"-diamine, N,N'-diphenyl-N,N'-bis(3-methylphenyl)-(1,1'-biphenyl)-4,4'-diamine, N,N'-bis(3-methylphenyl)-N,N'-bis(phenyl)-spiro, N,N'-bis(4-(N,N'-diphenyl-amino)phenyl)-N,N'-diphenylbenzidine, 4,4',4'-tri(N-carbazolyl)-triphenylamine, 4,4',4'-tri(carbazol-9-yl)triphenylamine, trichloroisocyanuric acid, terbium-doped phosphate-based green luminescent materials, 2,3,6,7,10,11-hexacyano-1,4,5,8,9,12-hexaazatriphenylene, 4,4',4'-tri(N-3-methylphenyl-N-phenylamino)triphenylamine, poly[(9,9'-dioctylfluorene-2,7-diyl)-co-(4,4'-(N-(4-sec-butyl)- phenyl) diphenylamine))], poly(4-butylphenyl-diphenylamine) (poly-TPD), poly[bis(4-phenyl)(4-butylphenyl)amine], polyaniline, polypyrrole, poly(p-phenylene vinylene), poly(phenylene vinylene), poly[2-methoxy-5-(2-ethylhexyloxy)-1,4-phenylene vinylene] and poly[2-methoxy-5-(3',7'-dimethyloctyloxy)-1,4-phenylene vinylene], copper phthalocyanine, aromatic tertiary amines, polynuclear aromatic tertiary amines, 4,4'-bis(p-carbazolyl)-1,1'-biphenyl compounds, N,N,N',N'-tetraaryl At least one of benzidine, PEDOT, PEDOT:PSS and its derivatives, PEDOT:PSS derivatives doped with s-MoO3, poly(N-vinylcarbazole) (PVK) and its derivatives, polymethacrylate and its derivatives, poly(9,9-octylfluorene) and its derivatives, poly(spirofluorene) and its derivatives, N,N'-di(naphthalene-1-yl)-N,N'-diphenylbenzidine, spiro NPB, nano-polycrystalline diamond, microcrystalline cellulose, tetracyanoquinodimethane, doped graphene, undoped graphene, C60, transition metal oxides, transition metal sulfides, and transition metal tin compounds.

14. A display device, characterized in that: The display device comprises the optoelectronic device according to any one of claims 12 to 13.

Citation Information

Cited By

  • High-temperature conductive graphene liquid medicine and preparation method thereof

    CN120824060A